Optimalisasi Pembelajaran Berbasis Masalah Berbasis Website di Sekolah Menengah Pertama - Irawan, Safri; Haryani, Meri; Wahyuni, Hera; Mile, Rifky; Haryanto, Arief Ibnu; Ikhsan, Haerul; Parengkuan, Meyke; Prasetyo, Agung; Pakaya, Rosbin (Jambura Arena Pengabdian, 2024)
In the Society 5.0 era, digital technology has changed the way humans interact and work, including in the education sector. This article discusses the implementation of Problem-Based Learning (PBL) at SMP Negeri 6 Gorontalo City by utilizing websites as a tool to increase students' learning readiness. The aim of this service is to empower teachers through training and providing digital resources that support the implementation of PBL. The methods used in this service include teacher training and implementing a website as a learning platform. This service was carried out for one month and involved 51 teachers from various backgrounds. The evaluation results show that the use of websites in PBL not only increases student motivation and involvement in the learning process, but also makes it easier for teachers to deliver material and manage the class. The website provides an interactive and collaborative platform that enriches students' learning experience and prepares them to face the challenges of the digital era. In conclusion, the implementation of website-based PBL has succeeded in increasing students' learning readiness and changing teachers' teaching methods positively. Measuring tools used to determine the success of this activity include teacher satisfaction surveys, classroom observations, and assessing student engagement and motivation through questionnaires and interviews.